The Influence Of The Board Of Directors’s Size, Independent Board Of Commissioners, Audit Committee, Managerial Ownership, Institutional Ownership, And Foreign Ownership On Firm Value - Hasnah, Alfilailatul; Wulandari, Putu Prima (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2026)
This study aims to examine the effect of the board of directors’ size, independent board of commissioners, audit committee, managerial ownership, institutional ownership, and foreign ownership on firm value measured by Tobin's Q. The unit of analysis in this study includes all company sectors listed on the Indonesia Stock Exchange (IDX) in 2023. The sample was selected using purposive sampling, resulting in 179 companies. The data analysis method employed is multiple regression analysis using Statistical Product and Service Solutions (SPSS) version 24. The results indicate that independent commissioners, audit committees, managerial ownership, institutional ownership, and foreign ownership have significant positive effects on firm value, whereas board size has a significant negative impact. These findings suggest that firm value can be enhanced by increasing the proportion of independent commissioners, audit committees, managerial ownership, institutional ownership, and foreign ownership. However, a larger board size may reduce firm value.